Document examination in criminalistics and forensic sciences: New approaches and modern technologies - Shepitko, Valery; Shepitko, Mykhaylo (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Document examination in criminalistics and forensic sciences is an activity required during the investigation and/or judicial proceedings. Using the full potential of investigative actions in document examination is an important source of evidence, which makes it possible to put the crime investigation on the right path. It is extremely important to resolve issues related with the expert examination of documents. Since the technical study of documents is the most common type of forensic studies, the article notes its transformation both towards expanding and restricting its volume. Moreover, the authors give indication of the new paradigm emerging in the examination of documents and their new forms, which highlights the need for developing new approaches and using different techniques and legal frameworks. Another important aspect is the protection of the judicial proceedings from false and erroneous forensic expert reports. To this end, forensic experts are warned of possible criminal liability and are sworn in. It is worth noting that these mechanisms are not always effective and the use of additional legal and managerial decisions in this regard is required. Forensic experts’ false and erroneous reports may be the subject of investigative actions and expert investigations.
Keywords: badanie dokumentów; badanie kwestionowanych dokumentów; raport kryminalistyczny; kryminalistyka; biegły sądowy